The flow/fund model of Conga: Exploring the anatomy of environmental conflicts at the Andes-Amazon commodity frontier (2014)
This paper aims to contribute toward improved understanding of complex ecological distribution conflicts at the commodity frontiers, where increasing metabolism in industrial societies is leading to increased environmental destruction in resource-rich countries throughout the world. The focus of this paper is the Conga gold mine project in northern Peru, where there have been violent clashes between the Minera Yanacocha mining company and the local population, represented mainly by campesinos that live in the highlands of the Andes–Amazon region. We do this by using the flow/fund model developed by Georgescu-Roegen and extended by Giampietro and Mayumi, to help us trace the anatomy of this conflict, using simplified representations of the central economic processes involved: gold mining and milk production. By complementing the concept of Ricardian land—an indestructible fund—with the concept of land materials, which is susceptible to qualitative change, and therefore can be either a fund or a flow element of the economic process, we illustrate that the gold extraction process, which treats this land material as a flow, stands in conflict with the milk production process, at least in part, because that process is using these land materials as a fund, i.e., in order to make production possible. The paper employs the concept of environmental valuation triadics, developed by Farrell, in order to explore how the boundaries—physical frontiers and temporal durations—of a specified economic process are related to flow/fund element identities. We conclude with some reflections on potential future applications for the methods employed and on the implications of our analytical results.